Bioanalytical method validation for determination of rosmarinic acid in simulated biological media using hplc - Kotchaphan Chooluck (2022)
Objective: This study aims to develop and validate a simple, rapid and accurate HPLC method for the determination of rosmarinic acid (RA), an active marker of Thunbergia laurifolia (TL) tea, in Hank's Balanced Salt Solution (HBSS) using HPLC. Methods: The separation was performed using a Xterra® C 18 reversed-phase column (150 × 3.9 mm, 5 µm). The mobile phase consisted of 0.5% (v/v) glacial acetic acid (A) and acetonitrile (B). The flow rate was 1 ml/min and detection was carried out at 330 nm with UV-visible spectrophotometer. The method was validated according to the US FDA guidance on bioanalytical method validation in 2018. Results: The method was successfully validated in the range of 50-500 ng/ml of RA. Intra-and inter-day precision ranged from 1.6 to 2.1% and 1.4 to 4.5%, respectively. Intra-and inter-day relative errors (% bias) were less than 7.6 and 3.6%, respectively. In addition, it was found that the stability of RA in HBSS could be dependent on the pH and temperature. Conclusion: The developed method met the validation requirements and could be further applied to the permeability study of RA using an in vitro Caco-2 cell monolayer model.